Practical algorithms for 3D computer graphics - Ferguson, R. Stuart (Robin Stuart), 1953- (CRC Press, 2014)
"Practical Algorithms for 3D Computer Graphics, Second Edition covers the fundamental algorithms that are the core of all 3D computer graphics software packages. Using Core OpenGL and OpenGL ES, the book enables you to create a complete suite of programs for 3D computer animation, modeling, and image synthesis.Since the publication of the first edition, implementation aspects have changed significantly, including advances in graphics technology that are enhancing immersive experiences with virtual reality. Reflecting these considerable developments, this second edition presents up-to-date algorithms for each stage in the creative process. It takes you from the construction of polygonal models of real and imaginary objects to rigid body animation and hierarchical character animation to the rendering pipeline for the synthesis of realistic images.New to the Second EditionNew chapter on the modern approach to real-time 3D programming using OpenGLNew chapter that introduces 3D graphics for mobile devices New chapter on OpenFX, a comprehensive open source 3D tools suite for modeling and animationDiscussions of new topics, such as particle modeling, marching cubes, and techniques for rendering hair and furMore web-only content, including source code for the algorithms, video transformations, comprehensive examples, and documentation for OpenFXThe book is suitable for newcomers to graphics research and 3D computer games as well as more experienced software developers who wish to write plug-in modules for any 3D application program or shader code for a commercial games engine"--